Penerapan Theta* Pathfinding untuk Navigasi Non-Player Character pada Gim Maze - Akbar Ramadhan; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Video Game development has grown as time passes, with an example of Computer Graphic which resulted in products that are almost on par with reality. Varieties of game engine available for developers helps the growth of game development and game industries. One aspect of game development which has also grown is Artificial Intelligence (AI). AI has the ability to give the game a feeling of reality, with its intelligence that is almost like that of a human. One use of AI that is frequently used is Pathfinding. Pathfinding is a searching method from one point to another driven by AI. A* is the most frequently used pathfinding, because A* is guaranteed to give the optimal path. However, the generated path is not always the closest path, as there are other omitted paths which can optimized further with post-processing technique. There are lots of alternative beside A*, one example is Theta* Pathfinding, which is an algorithm that was developed from A*. This research discusses Theta* Pathfinding and its performance compared to basic A* Pathfinding in a maze game. The result of this research shows that Theta* Pathfinding generates a shorter, more optimal route and a shorter time compared to that of A* Pathfinding.